Social and solidarity economy in the development of Antioquia: an approach - Vélez Tamayo, Julián Mauricio (Cooperativismo & Desarrollo, 2024)
This document aims to show an initial exercise where the relationship between the Social and Solidarity Economy with Development in the department of Antioquia is verified, an exercise using the information reported in UAEOS (Special Administrative Unit of Solidarity Organizations) for 2019. A series of regressions in Ordinary Least Squares on a cross-sectional database for the year mentioned was performed. A statistically significant relationship was found between the number of Social and Solidarity Economy entities existing in the analyzed municipalities and the level of Gross Domestic Product as an initial measure of development. In other variables, the relationship is not significant except for the number of partners, excluding the city of Medellín from the analysis.